Percepção de nefrologistas brasileiros sobre cuidados paliativos em pacientes renais crônicos - Bueno, Maria Eduarda (2024)
Palliative care has been increasingly used to improve the well-being and quality of life of people who have a serius, life-threatening illness. A multidimensional palliative approach can and should be integrated in different contexts to reach patients with life- limiting chronic diseases, such as patients with advanced chronic kidney disease (CKD), especially those on dialysis. A relevant consideration in the CKD context is that the accelerated pace of population aging constitutes an important public health problem, as the care of elderly people with multiple comorbidities becomes more complex and difficult, as damage to various organs appears. Thus, many factors contribute to uncertainty about the balance between the benefits and harms of dialysis in this population. The main objective of this study was to analyze the perceptions of Brazilian nephrologists about palliative care in patients with chronic kidney disease and about the inclusion or withdrawal of patients on dialysis for conservative treatment through a quantitative, cross-sectional, survey-type study. After the necessary ethical approvals, a questionnaire based on the literature and validated by a committee composed of six experts was applied online to nephrologists in the first half of 2023. The results were: 273 respondents presented sociodemographic characteristics equivalent to those found in the Medical Demographics of the Brazilian Federal Council of Medicine [CFM] for the specialty. The majority of nephrologists believe that palliative care is related to terminality and not to the care since the beginning of the disease and associate palliative care with a dignified death and with orthothanasia. In addition, there are no protocols and tools to assist health professionals in the decision to withdraw or not include hemodialysis patients, and this should be seen as an important warning for the specialty community and future studies to create them. There are clear gaps in undergraduate and medical residency so that palliative care (whether or not the patient is on dialysis) can be implemented with solid knowledge, skills and attitudes that allow for good communication; quality of life, more than its quantity; symptom control; respecting the autonomy of the person with CKD, in a perspective centered on their well-being and on decisions shared with their family/caregivers/multidisciplinary team. However, there is an understanding of its importance and motivation to learn. The lack of legislation, structures and teams dedicated to palliative care in SUS [Brazilian Unified Health System] and heath insure is perceived by most nephrologists. Specific research in palliative care in CKD is necessary in Brazil, particularly in the world, that subsidize planning and strategies to overcome problems that will be growing and frightening. This research provided support for an in-depth analysis of nephrology supportive care for people with CKD. Public policies should be designed to improve the panorama of the growing need for physicians and health teams trained to identify, plan and follow up patients with CKD who opt for comprehensive palliative care or conservative support